A National Multicenter Study on Initial Antiviral Treatment Preferences on Chronic Hepatitis B: Entecavir Versus Tenofovir Disoproxil Fumarate - Yamazhan, Tansu; Zerdali, Esra; Onlen, Yusuf; Tosun, Selma; Gunal, Ozgur; Batirel, Ayse; Guner, Rahmet (Aves, 2026)
Background/Aims: Selecting the initial antiviral regimen for chronic hepatitis B (CHB) requires balancing patients' comorbidities and long-term safety. This study examines the differences in patient and disease-related factors that guide clinicians to prescribe either entecavir (ETV) or tenofovir disoproxil fumarate (TDF) as the initial treatment. Materials and Methods: The study included treatment-na & iuml;ve CHB patients aged 18 or older who had been diagnosed for at least 1 year since 2010 and initiated on antiviral therapy. The data included variables such as age, gender, body mass index (BM!), comorbidities, liver disease activity, biopsy results, cirrhosis, hepatic steatosis, hepatitis B e-antigen status, hepatitis B virus DNA levels, triglycerides, cholesterol, renal function, and baseline bone mineral density (BMD), which were assessed by dual-energyx-ray absorptiometry (DEXA). Results: Among 2259 patients (61.6% male), 1270 patients (56.22%) received TDF, while 989 patients (43.78%) received ETV as first-line therapy. The TDF was more commonly prescribed to patients with a lower BM! (median 25.7 vs. 26.2, P = .001) and lower baseline creatinine (0.75 vs. 0.80 for ETV, P < .001). Clinicians preferred ETV among patients with an estimated glomerular filtration rate (eGFR) < 60 (n = 36), (P < .001). The BMD was evaluated in 365 patients (16.3%). The DEXA scans were performed for 116 patients (11.8%) in the ETV group and 249 patients (19.8%) in the TDF group (P < .001). Conclusions: This national multicenter study emphasizes that patient-related factors, including gender, age, baseline renal function, and liver disease severity, significantly influence the choice of first-line antiviral therapy for CHB, often outweighing disease-specific factors.
Keywords: Chronic hepatitis B; entecavir; tenofovir disoproxil fumarate